PERAN PEMERINTAH DESA KOTO TIBUN KECAMATAN KAMPAR KABUPATEN KAMPAR DALAM MENINGKATKAN POTENSI PERIKANAN TAHUN 2011-2012 - Rostina Norma Fitri; Raja Muhammad Amin, (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
In Kampar Regency is the producer of aquaculture products with thehighest ratings supported the existence of great potential in the development ofsuperior commodities especially aquaculture sector. Approximately 90 percent ofaquaculture production came from Riau Province Kampar it is not wrong if calledKampar is aquaculture Riau lives. Licensing fisheries management in KamparDistrict contained in Kampar District Regulation No. 28 of 2009 ConcerningLicensing Services And Business Recommendations and / or activity of theEnvironment Division. Kampar was umpteen of county and city in Riau Provincewhich has 2,112 hectares of fish ponds and rivers and reservoirs kerambah 410.Unfortunately the potential of fisheries, particularly aquaculture in KamparRegency maximum untapped. These results indicate that there is an important roleTibun Koto Village Government in improving fisheries potential, namely throughcoordination with the Department of Fisheries, as well as factors that affect themiraculous is Factor Human Resources, Regulatory Factor (rules), OrganizationalFactors, Factors Administrative, Budget factor. This research was conducted inthe District Fisheries Office and the Office of Rural Koto Kampar Tibun. The dataused in this research is data Primary and secondary data. The technique ofcollecting data through in-depth interviews and documentation. This study used aqualitative descriptive method of data collection due informant interviewsconducted with the depth of the informants related. So that the formulation of theproblem in this case is how the role of village government Tibun Koto KamparKampar district in improving the potential of fisheries in 2011-2012 and pakahfactors affecting the role of Village Government Tibun Koto Kampar Kampardistrict in improving the potential of fisheries in 2011-2012.Keywords: Role, Potential, Fishing